Multi-Agent Programming: Languages, Tools and Applications - El Fallah Seghrouchni, Amal.; Dix, J<U+00fc>rgen.; Dastani, Mehdi.; Bordini, Rafael H. (Springer US, 2009)
This book, along with the previous work Multi-Agent Programming: Languages, Platforms and Applications, provides and maintains an updated state of the art related to Multi-Agent Systems programming. This volume includes chapters describing programming languages and their platforms, discussing the features of the languages, the communication mechanisms they provide, their underlying execution model and interpreters, their expressiveness, verification possibilities, and the software engineering principles that they follow. Additional chapters present and evaluate various types of development tools such as debugging tools, testing tools, modelling tools, environment artifacts, and integrated development environments (IDEs). Also included is a chapter dedicated to a specific application providing a multi-agent environment for negotiation; the chapter describes how the target multi-agent system has been designed and specified. Specific topics featured include: MetateM, an approach to capture the dynamic nature of agents and their groups the IndiGolog language, its implementation, and applications that have been realized with it Brahms, a multi-agent modelling language for simulating human work practice, currently used at NASA GOAL , a high-level language to program rational agents that derive their choice of action from their beliefs and goals JIAC, a Java-based agent framework with an emphasis on industrial requirements such as software standards, security, management, and scalability Agent Factory, a cohesive framework for the development and deployment of multi-agent systems a tool for generating test cases for unit testing of agent-based systems, and a tool for debugging agent programs by monitoring a running system a platform and infrastructure that provide a general-purpose programming model for building shared computational worlds (called <U+0018>work environments<U+0019>) that agents, possibly belonging to heterogeneous agent platforms, can exploit to work together within a Multi-Agent System a detailed investigation of the landscape of available agent-oriented development tools System for Analysis of Multi-Issue Negotiation (SAMIN), which offers a negotiation environment that supports and facilitates the creation of various negotiation setups and discusses some of the experimental results an appendix, summarizing each of the six agent programming languages presented in the book Multi-Agent Programming: Languages, Tools and Applications presents a number of mature and influential multi-agent programming languages, platforms, development tools and methodologies, and realistic applications, summarizing the most current developments in an accessible manner for professionals and computer science students at all levels.